Effects of dietary nucleotides levels on whole body composition of orange spotted grouper (Epinephelus coioides) - B. Bahmani email ; A. Zariffard; M. Khodadadi; N. Mahmoudi; A. Ojeefard (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2011)
This research was carried out for 10 successive weeks (2 weeks for adaptation and 8 weeks for culture) in summer 2008 at Abzisytan Shrimp Hatchery Center in Bushehr province. The effects of dietary nucleotides at 5 levels including 0.0% (control), 0.15%, 0.25%, 0.35% and 0.5% on the growth performance and whole-body composition of Epinephelus coioides was investigated. Juvenile fish specimens with average weight of 10.70Â±0.29g were fed by experimental diets for 8 weeks. The trial was carried out in 300 liter fiberglass tanks. The highest protein content was observed in 0.15% diet nucleotide and the highest fat in 0.15% and 0.25% diet nucleotide which showed significant difference with th